Calcifications in soft tissues of the head and neck region in a sample of Brazilian adults - Mota de Oliveira Kublitski, Prescila (2024)
Objective: To identify calcifications in the soft tissues of the head and neck region in digital panoramic radiographs of Brazilian adults. Materials and methods: In this cross-sectional study, 384 examinations of individuals of both sexes, aged between 18 and 80 years, were analyzed for carotid artery calcifications, sialoliths, phleboliths, tonsilloliths, anthroliths, calcifications of the trityceous cartilage, calcifications of the styloid ligament and calcified lymph nodes. The association with sex and age was also studied. Data were analyzed using SPSS® version 23.0, with a significance level set at 5%. Results: Calcifications were identified in 53 examinations (13.80%). Styloid ligament calcification was observed in 24 cases (6.20%), followed by anthroliths (2.40%). Sialoliths and tonsilloliths were present in 6 cases each (1.60%). No calcified lymph nodes or phleboliths were identified. Despite the lack of significant association with sex and age (p > 0.05), females, white individuals and those in the fourth decade of life were more frequently affected. Conclusions: The frequency of calcifications in this sample was high, particularly for stylohyoid ligament calcifications and anthroliths, although no associations with sex and age were found.